Innovation in hospital: Learning from Malcolm Baldrige Awards latest winners in healthcare - Budi Harsanto (Proceeding of International Conference on Science, Health, And Technology, 2021)
The purpose of this paper is to take lessons about innovations made by the latest winners of the Malcolm Baldrige National Quality Award (MBNQA) in the healthcare sector. In 2018-2019 three hospitals won the awards, and all have the excellence in innovation. The method used is qualitative by analyzing the three winning organizations’ MBNQA application documents related to innovation and other sources as supporting and triangulation materials. The analysis was carried out using content analysis guided by the innovation management measurement framework. The analysis results show that these organizations emphasize the importance of innovation input and knowledge management for successful innovation implementation/commercialization. This paper’s uniqueness is innovation management’s concept involvement and is carried out in recent healthcare organization cases.